Microbiological analysis of urinary tract infection in diabetic patients - Otta, Sarita; Swain, Bichitrananda; Bhoi, Priyadarshini (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus is a predisposing condition to different infections especially the complicated urinary tract infection (UTI). The susceptibility pattern of organisms in diabetics is different from their counterparts. So, there is always a dilemma while administering empirical regimen for UTI in diabetics. The study aims to find the common organisms implicated in the UTI in diabetic patients and their sensitivity pattern. Methods: Properly collected urine specimen from all the diabetic (cases) and non-diabetic (controls) patients included in this study was processed. Sensitivity pattern and extended spectrum beta lactamase (ESBL) production for the isolated uropathogens was noted. Results: E. coli was the most common organism isolated from both 68 cases and 85 controls in this study. Most of UTI patients with diabetes, 46 (67.7 %) had uncontrolled blood sugar level. Diabetics are more prone for catheter associated UTI (CAUTI) and fungal UTI. Most of the E coli and Atypical E coli isolated were ESBL positive for the diabetic patients (60.5%) than that for the non-diabetics (40.4%). Antimicrobial resistance pattern was similar in both the groups with maximum patients’ sensitivity to tigecycline, colistin, fosphomycin and least susceptibility to cefixime. Both E. coli and Klebsiella also showed high resistance to the fluoroquinolones. Conclusions: E. coli is the predominant uropathogen for both the diabetic & non-diabetic cases. But diabetics are more prone to get ESBL positive UTI. CAUTI and the fungal UTI are more common in diabetics. Diabetic condition does not affect the antimicrobial resistance pattern of uropathogens. But their rising resistance to fluoroquinolones, cephalosporins is a matter of concern while prescribing empiric regimen.